Modulation of Mammalian Cell Behavior by Nanoporous Glass. Issue 7 (7th May 2021) - Emmert, Martin; Somorowsky, Ferdinand; Ebert, Jutta; Görick, Dominik; Heyn, Andreas; Rosenberger, Eva; Wahl, Moritz; Heinrich, Doris
Abstract: The introduction of novel bioactive materials to manipulate living cell behavior is a crucial topic for biomedical research and tissue engineering. Biomaterials or surface patterns that boost specific cell functions can enable innovative new products in cell culture and diagnostics. This study investigates the influence of the intrinsically nano‐patterned surface of nanoporous glass membranes on the behavior of mammalian cells. Three different cell lines and primary human mesenchymal stem cells (hMSCs) proliferate readily on nanoporous glass membranes with mean pore sizes between 10 and 124 nm. In both proliferation and mRNA expression experiments, L929 fibroblasts show a distinct trend toward mean pore sizes >80 nm. For primary hMSCs, excellent proliferation is observed on all nanoporous surfaces. hMSCs on samples with 17 nm pore size display increased expression of COL10, COL2A1, and SOX9, especially during the first two weeks of culture. In the upside down culture, SK‐MEL‐28 cells on nanoporous glass resist the gravitational force and proliferate well in contrast to cells on flat references. The effect of paclitaxel treatment of MDA‐MB‐321 breast cancer cells is already visible after 48 h on nanoporous membranes and strongly pronounced in comparison to reference samples, underlining the material's potential for functional drug screening. Abstract : Nanoporous glass membranes present nanoscale topographic cues that act as bioactive triggers to influence cellular cascades for the regulation of cell functions such as adhesion, proliferation, gene expression, and differentiation. In cell culture applications, they can be used for the buildup of complex functional assays that benefit from a more physiological cell behavior than simple 2D cultures.